Development of Serious Games for Music Education - Adriano Baratè; Mattia G. Bergomi; Luca A. Ludovico (Je-LKS: Journal of E-Learning and Knowledge Society, 2013)
Serious games have proved to be an effective educational tool in many fields. The first goal of this paper is to illustrate some possible applications to music and their advantages. Moreover, music can be characterized by heterogeneous multimedia contents. Among the different facets music information is made of it is worth citing music symbols, their graphical representations as scores, their audio renderings as tracks, etc. The international standard known as IEEE 1599 is an XML multilayer format for heterogeneous music contents, and describes such different aspects in an integrated and synchronized context. Making relationships among music contents explicit provides a potentially rich educational environment. Consequently, this paper discusses the concept of multilayer learning object, introduces the IEEE 1599 standard, and finally shows some applications and case studies.